Centrifugal pump performance characteristics for domestic application - Aisyah, Jilani; Akhtar Razul, Razali (EDP Sciences, 2018)
Water pressure problems at home can be quite frustrating in daily life which is comes in different ways of complication. It may take forever for the faucets to fill a bathtub, or a slow spray shower head and longer time taken for the washing machine to run a cycle. The problem can be fixed by installing a pressure booster pump. This research is embarked to study on a centrifugal pump performance with a view to analyse pressure built-up and flowrate in pipe at fixed speed. A simple and inexpensive test rig is developed to resemble water distribution for domestic use; i.e. house application. The method is then experimentally validated to measured and analysed the pump performance such as water pressure, water flowrate, power of pump and pump speed. Since the centrifugal pump are added, the pump is able to boost the water flowrate. However, since the centrifugal pump work at constant speed, the water pressure in pipe is high when the water demand is low. The maximum pressure inside the pipe was 28.24 psi which quite high and exceed the piping standards. Power consumption also remained constant approximately 0.500 kWh when water demand was low which led to energy wastage.